PENGARUH INTENSI WHISTLEBLOWING TERHADAP PENCEGAHAN KECURANGAN DENGAN RELIGIUSITAS SEBAGAI PEMODERASI (STUDI KASUS PADA PEGAWAI SKPD PEMERINTAH KABUPATEN ACEH UTARA) - Nurrahma, Fanni; Abdullah, Syukriy; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to examine the effect of whistleblowing intention on fraud prevention with religiosity as moderating at Aceh Utara Regency. The research uses primary data and the respondents were 99 employees of SKPD (local government agencies) at Aceh Utara Regency. Data collection was carried out by distributing questionnaires using google form to respondents. This study used a simple random sampling method where the sample was taken randomly. The data analysis method used is simple linear regression with SPSS 26. The results of the study indicate that whistleblowing intention has a positive effect on fraud prevention, while religiosity as moderating has no effect on the connection between whistleblowing intention and fraud prevention. Discussions, limitations, and recommendations are presented at the end of this paper.